William Kemp, Shakespeare’s Star Comedian, Morris Dancers, and Robin Hood: Emblematic Images of the Body - Streitman, Krisztina (FOCUS: Papers in English Literary and Cultural Studies, 2024)
William Kemp, the acrobatic Morris dancer, and Shakespearean comic star, and the historical and emblematic figure of Robin Hood and his legend—along with the methods of communication they represented—had symbolic significance in early modern popular culture. Kemp and the figure of Robin Hood share many characteristic features: their expressive dancing and fighting, the gestural, spontaneous genres of contemporary entertainment they purposefully chose, the oral, popular culture they represented, and their unique physical appearance. We can glean information about the above-mentioned communicational forms from the following invaluable visual sources: the Tollet window, the front page of Kemp’s diary, Nine Daies Wonder, and several illustrations of the ballads of Robin Hood. We can also find the mainstream of the Robin Hood tradition that Kemp also represented: comedy, parody, transgression, and farce. These genres are intimate and dynamic parts of medieval ballads and popular films as well. In my essay, I aim to highlight the Robin Hood that Kemp might have embodied in his performances.